Tipologi Wacana Keislaman Yogyakarta, Studi Terhadap Buletin-buletin Jum'at di Jogja - Ahmad, Nyarwi (Centre for Islamic Studies, Universitas Islam Indonesia, 2011)
The topic of the study was Tpology of Islamic Discourse of Yogyakarta: A Study of Friday Prayer Bulletins in the Special Dictrict of Yogyakarta.